2019
DOI: 10.30534/ijatcse/2019/1481.32019
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Continuance Intention of a Cloud-Based Virtual Learning Environment with Psychological Ownership and the Technology Acceptance Model

Abstract: This study investigated teachers' intention to continue using a cloud-based Virtual Learning Environment (VLE) by incorporating the theory of psychological ownership and the Technology Acceptance Model (TAM). Psychological ownership refers to a sense of ownership where people feel psychologically attached to a particular object, and this concept is becoming increasingly relevant in technology adoption research. The study proposed that such phenomenon can also occur when teachers use a cloud-based VLE. Hence, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…A total of 94 users who participated and used the application for two weeks, completed a survey of 18 items to determine the factors that affect application acceptance showed that compatibility, perceived benefits, and perceived ease of use significantly influence behavioral intentions to use cellular obesity management applications [6]. In studies using cloud based virtual learning, it is stated that application functions are relatively easy to navigate, which leads to continued use of the application [22]. Nowadays UX (user experience) which is related to ease of use becomes very important in the development of a website, where this user experience affects the acceptance of use on the web [23].…”
Section: Cmentioning
confidence: 99%
“…A total of 94 users who participated and used the application for two weeks, completed a survey of 18 items to determine the factors that affect application acceptance showed that compatibility, perceived benefits, and perceived ease of use significantly influence behavioral intentions to use cellular obesity management applications [6]. In studies using cloud based virtual learning, it is stated that application functions are relatively easy to navigate, which leads to continued use of the application [22]. Nowadays UX (user experience) which is related to ease of use becomes very important in the development of a website, where this user experience affects the acceptance of use on the web [23].…”
Section: Cmentioning
confidence: 99%
“…Virtual assistants can have an avatar model that facilitates communication between users who use interactive and can represent interactive types that are easy and fast in providing quality information [7]. Virtual assistants can be built using web-based internet infrastructure by providing learning engines on servers on the internet [8]. Models like this can use cloud computing technology to make it more efficient in the use of processors, memory, and bandwidth [9].…”
Section: Literatur Reviewmentioning
confidence: 99%